As relações entre soberania e governo em Jean-Jacques Rousseau - Correia, André Rezende Soares (2021)
This work deals with the relations between sovereignty and government as from the political thought of the philosopher Jean Jacques-Rousseau. The theme emerges from the concern demonstrated by the author in ensuring that the expression of the general will be the source of the laws to be applied by rulers in their role of ministers subordinated to such will. Thus, by taking as a reference the principles of political right elaborated by Rousseau, essentially in the Social Contract, without forgetting his other writings, his ideas are analyzed concerning the social contract as the association's act that establishes a legitimate and secure civil order, for the purpose of guarantee freedom and equality for citizens as members of the State. With this basis, the relations between sovereignty and government are focused in order to understand how they can be useful, stable, balanced and institutional, respecting the respective competences of these entities. Thus, the work develops in three chapters. The first encompasses the theory of the social contract: the institution of the civil order, the legitimacy of the general will and of popular sovereignty, which ensure the freedom and plurality of interests. Thereafter, the second chapter reflects more directly on the government, its function in the republic and its different forms, with the intention of discussing how he must act for the benefit of political community, and also what are the problems inherent in their relations with the sovereign. Finally, the third chapter contemplates some of the republican mechanisms indicated by Rousseau to promote state's conservation, mainly taking into account the dangerous tendency of the government to try and overlap popular sovereignty, confusing its public power, given to it to enforce laws, with the sovereign acts of the general will.